Transcatheter Closure of a Paravalvular Leak Guided by Transesophageal Echocardiography and Three-Dimensional Printing - Xu, Chennian; Liu, Yang; Zhai, Mengen; Jin, Ping; Li, Lanlan; Ma, Yanyan; Yang, Jian (Frontiers in Cardiovascular Medicine, 2022)
Background Percutaneous paravalvular leak (PVL) closure is a technically challenging procedure because of the specific anatomy after surgery and complex catheter techniques required. The transesophageal echocardiography (TEE) and three-dimensional(3D) printing might be helpful to identifying complex anatomical structures and the procedural design. Objectives The purpose of this study was to review the experiences in transcatheter closure of PVL guided by transesophageal echocardiography and three-dimensional printing. Methods From January 2015 through December 2020, 166 patients with PVL after surgical valve replacement underwent transcatheter closure. Among these patients, 68 patients had preoperative transesophageal echocardiography and three-dimensional printing assistances. The catheter techniques, perioperative characters and prognosis were reviewed. The median follow-up was 36 (3-70) months. Results The acute procedural success was achieved in 154/166(92.8%) patients, with 64/68(94.1%) in patients with TEE＆3D guiding and 90/98(91.8%) in patients with transthoracic echocardiography(TTE). There was no hospital death in all cases. All percutaneous procedures were performed with local anesthesia except for thirteen trans-apical cases with general anesthesia. Multiple approaches were performed, including trans-femoral, trans-apical and trans-septal via arterious-venous loop. And multiple devices were deployed, including ADO, ADO II, PLUG II, PLUG III and mVSD occluders. TEE＆3D guiding cases had shorter procedural time with [35-202(61±23) vs. 38-313(105±53), P<0.05] min than TTE guiding cases. The fluoroscopic time was also shorter in TEE＆3D guiding cases with [8-49(18.5±11.4) vs. 10-140(27.3±15.6), P<0.05] min than one in TTE guiding cases. The complications included recurrent hemolysis, residual regurgitation, acute renal insufficiency and anemia. There was no significant difference in the incidence of complications between two groups. Conclusions The transesophageal echocardiography and three-dimensional printing have advantages in guiding transcatheter closure of PVL with shorter procedural and fluoroscopic time. This minimally invasive treatment could provide reliable outcomes in selected patients.